PENGARUH PENGALAMAN KERJA, PENGEMBANGAN KARIR DAN MOTIVASI TERHADAP KINERJA KARYAWAN ASTRA MOTOR BATUBULAN, GIANYAR - I Kadek Agus Engky Wira Pratama; Made Ika Prastyadewi; I Nyoman Resa Adhika (VALUES, 2023)
Human resources within the company need to be managed professionally so that a balance can be realized between the needs of employees and the demands and capabilities of the company, as well as the ability of human resources which will later determine the success of the company. This study aims to determine the effect of work experience, career development and motivation on employee performance. This research was conducted at Astra Motor Batubulan, Gianyar using a sample of 34 employees. The sampling technique used is the census method. Data collection was carried out through observation, interviews, questionnaires and documentation. The data analysis technique used was multiple linear regression analysis which was processed using SPSS version 25 software. Based on the analysis results, this study shows that work experience has a positive and significant effect on employee performance at Astra Motor Batubulan, Gianyar. This means that the better the work experience, the better the performance of employees at Astra Motor Batubulan, Gianyar. Career development has a positive and significant effect on employee performance at Astra Motor Batubulan, Gianyar. This means that the better the career development, the better the employee performance at Astra Motor Batubulan, Gianyar. Motivation has a positive and significant effect on employee performance at Astra Motor Batubulan, Gianyar. This means that the better the motivation, the better the performance of employees at Astra Motor Batubulan, Gianyar.